2016
DOI: 10.1080/00220388.2015.1060314
|View full text |Cite
|
Sign up to set email alerts
|

Is Women’s Ownership of Land a Panacea in Developing Countries? Evidence from Land-Owning Farm Households in Malawi

Abstract: Our analysis of a rich representative household survey for Malawi, where patrilineal and matrilineal institutions coexist, suggests that (a) in matrilineal societies the likelihood of high value crop cultivation by a household increases with the extent of land owned by males, while the income generated from high value crop production decreases with the amount of land owned by females (b) cultivation of high value crops increases household welfare. The policy implication is that facilitating female ownership of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…Consistently also, the differences in land ownership significantly contributed 19.64% of the total G. Empirically, [44] estimated a positive effect of land ownership on welfare. But contrary to this study, [48] found that ownership of land does not necessary improve women's welfare, instead, ensuring tenure security, access to complementary inputs and market are crucial to accrue the benefits of land ownership by women.…”
Section: Factorscontrasting
confidence: 92%
“…Consistently also, the differences in land ownership significantly contributed 19.64% of the total G. Empirically, [44] estimated a positive effect of land ownership on welfare. But contrary to this study, [48] found that ownership of land does not necessary improve women's welfare, instead, ensuring tenure security, access to complementary inputs and market are crucial to accrue the benefits of land ownership by women.…”
Section: Factorscontrasting
confidence: 92%
“…Outside these cultural domains, Malawi remains a state profoundly based on male authority. Agricultural services, institutions, and religious groups are all dominated by males, evidencing the persistence of gender inequalities (Peters 2010, Bhaumik, Dimova, & Gang 2016. In addition, recent evidence in the literature points out that farmers experiencing insecurity in land tenure are less willing to invest in agricultural technologies, soil conservation practices and climate-resilient technologies (Lovo, 2016).…”
Section: Hypothesismentioning
confidence: 99%
“…As the ability to decide on long-term transfer of land rights has been shown to affect investment decisions (Deininger and Jin 2006), individuals' ability to influence decisions on intergenerational land transfers is likely to affect their willingness to make non-observable investments. Place and Otsuka (2001), Lunduka (2009), Lovo (2016) and Bhaumik et al (2016) indeed argue that in matrilineal and matrilocal systems, the discrepancy between females' land ownership and males' social position and superior access to markets for inputs and outputs impedes land-related investments.…”
Section: Nature and Relevance Of Land Rights In Malawimentioning
confidence: 99%
“…Although manure use is our preferred indicator, its short-term productivity impact in a setting dominated by subsistence cultivation of maize may be limited. We thus use adoption of cash crops as a second indicator that has been reported as key to moving out of subsistence and increasing household income (Bhaumik et al 2016). Cash crops are also a key contributor to the gender differences in agricultural productivity (Kilic et al, 2015).…”
Section: Empirical Approachmentioning
confidence: 99%